The New Ray Bradbury Review, No. 2 - Touponce, William F. (Book collections on Project MUSE., 2014)
Like its pioneering predecessor, the one-volume review published in 1952 by William F. Nolan, "The New Ray Bradbury Review" contains articles and reviews about Bradbury but has a much broader scope, including a thematic focus for each issue. Since Nolan composed his slim volume at the beginning of Bradbury's career, Bradbury has produced hundreds of stories and half a dozen novels, making him one of this country's most anthologized authors. While his effect on the genres of fantasy, horror, and science fiction is still being assessed (see "Ray Bradbury: The Life of Fiction", The Kent State University Press, 2004), there is no doubt about his impact, and to judge from the testimony of his admirers, many of them now professional writers themselves, it is clear that he has affected the lives of five generations of readers. "The New Ray Bradbury Review" is designed principally to study the impact of Bradbury's writings on American culture and is the chief publication of The Center for Ray Bradbury Studies - the archive of Bradbury's writings located at Indiana University-Purdue University, Indianapolis. In this second number, scholars discuss Bradbury's view of the role of art and aesthetics in our modern technological lives. With the publication of his 1953 short story "The Day After Tomorrow in Nature", Bradbury began to articulate the ways in which science fiction could become a valid aesthetic response to the machine-oriented world. He asks and answers the questions: Can art still have a humanizing effect on culture and society? What is the role and responsibility of the artist to his public in an age of mechanical reproduction of art? And what of robots, aliens, and space flight, those icons of science fiction and fantasy? Bradbury's answers drew the attention of renowned Renaissance art historian and aesthetician Bernard Berenson, prompting him to begin a correspondence with Bradbury that spanned several years and is reproduced in this issue. Also included in this number is a fragment from Bradbury's screenplay "The Chrysalis" and a review of "Now and Forever", as well as insightful essays by Jon Eller and Roger Lay. Fans and scholars alike will welcome "The New Ray Bradbury Review", as it will add to the understanding of the life and work of this eminent author, whose work has received both a National Book Award and a Pulitzer Prize.